Politično-ekonomski temelji novega zahodnoafriškega naftnega mesta Sekondi-Takoradi - Obeng-Odoom, Franklin (Urbani izziv, 2012)
The origins, growth and trajectory of Sekondi-Takoradi, West Africa's newest oil city, are considered by using an "institutional-analytical" method of economic history. Particular attention is given to the role of ports, harbours and railways, and how they evolved and interacted with political economic institutions in the last 100 years. This omnibus historical analysis suggests that West Africa's newest oil city has come full circle. Its contemporary stature in national and international circles has a historical parallel in the 1920s when, as now, it captured national, regional and international attention. The evidence suggests that contemporary narratives that strike a determinist relationship between resource boom and social doom need to be reconsidered.
Keywords: Africa; Afrika; Gana; mesta; pristanišča; urbani razvoj